Layanan Pembiayaan Berbasis Teknologi Informasi Di BPRS Berdasarkan Prinsip Syariah - Tina, Dewi Agus; Zulaikha, Siti; Putri, Marisa (ASAS, 2022)
In Islamic finance, according to fiqh, interest in money is categorized as usury which means haram. The development of Islamic banking is quite rapidly spreading by providing banking services in accordance with the principles of Islamic sharia. The Sharia People's Financing Bank (BPRS) is the only BPR that operates with sharia principles in the city of Bandar Lampung. Technology-based financing on the system peer to peer (P2P) lending whose provisions refer to the DSN Fatwa concerning Technology-Based Financing Services Based on Sharia Principles. The problem in this study is how the implementation of information technology-based Murabahah contract financing services based on sharia principles at PT. BPRS Bandar Lampung? Is information technology-based financing services based on sharia principles at BPRS Bandar Lampung in accordance with DSN-MUI Fatwa No. 117/DSN-MUI/II/2018? The purpose of this study was to determine the implementation of information technology-based Murabahah contract financing services based on sharia principles at PT. BPRS Bandar Lampung. Then in the implementation of financing, it aims to find out that information technology-based financing services based on sharia principles at BPRS Bandar Lampung are in accordance with DSN-MUI Fatwa No. 117/DSN-MUI/II/2018. This study uses a descriptive-qualitative method with a normative-empirical approach based on a literature study by looking at the written regulations by identifying the appropriate theories, concepts, and sharia principles. The data used in this study are primary and secondary data. Sharia principles must be met in information technology-based financing service products based on sharia principles. Based on general guidelines on information technology-based financing service products based on sharia principles that exist at PT. BPRS Bandar Lampung is in accordance with the fatwa. Kata Kunci: The Sharia People's Financing Bank (BPRS), Technology-based financing, system peer to peer (P2P)